Prognostic Value of Human Epididymis Protein 4 in Acute Myocardial Infarction - Tang Y; Zhu WY; Peng SL; Huang S; Zhao QN; Tan SY; Yin ZH; Zhang Y; Peng JQ; Pan HW (International Journal of General Medicine)
Yi Tang,1,* Wen-Yu Zhu,2,* Si-Ling Peng,2,* Shuai Huang,2,* Qiu-Ni Zhao,3 Si-Yuan Tan,2 Zi-Hui Yin,2 Yan Zhang,1 Jian-Qiang Peng,1 Hong-Wei Pan1 1Department of Cardiology, Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Clinical Medicine Research Center of Heart Failure of Hunan Province, Hunan Normal University, Changsha, 410005, People’s Republic of China; 2Hunan Provincial People’s Hospital, The First Affiliated Hospital of Hunan Normal University, Hunan Normal University, Changsha, 410005, People’s Republic of China; 3Department of Anesthesia Operation, Maternal and Child Health Care Hospital of Hunan, Changsha, 410000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian-Qiang Peng; Hong-Wei Pan, Email pengjianqiang2021@foxmail.com; pan.hw@foxmail.comPurpose: To investigate the prognostic value of human epididymis protein 4 (HE4) in patients with acute myocardial infarction (AMI).Patients and Methods: A total of 212 consecutive patients diagnosed with AMI in the Department of Cardiovascular Medicine of Hunan Provincial People’s Hospital from June 2020 to May 2021 were enrolled. We determined plasma HE4 levels at baseline. The patients were followed up regularly and the occurrence of major adverse cardiac events (MACE) was recorded after discharge.Results: After a mean follow-up period of 242 (159– 427) days, 67 patients had MACE. Multivariate Cox regression analysis showed that HE4 was an independent predictor of MACE in patients with AMI [HR = 1.004 (1.002– 1.007), P = 0.002]. Kaplan-Meier survival curves showed that patients with HE4 levels > 532.9 pmol/L had higher MACE compared with patients with ≤ 532.9 pmol/L HE4 levels (HR=4.044, 95% CI 2.373– 6.890, P < 0.001). Receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) of HE4 for predicting MACE was 0.734 (95% CI: 0.669– 0.792, P < 0.001).Conclusion: Human epididymis protein 4 (HE4) might be a novel biomarker for predicting the prognosis of patients with AMI.Keywords: acute myocardial infarction, biomarkers, human epididymis protein